Heart-breaking aspirin interruption - Zeitouni, Michel; Montalescot, Gilles (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
The prescription of patients with coronary artery disease is a long one: 20% take 7 drugs or more every day, and patients aged 65 years or higher often take more than 10 drugs daily. This situation reflects the current trend in research and development of new drugs usually evaluated on top of the current standard of care. The pharmaceutical industry hardly supports drug withdrawal trials, whose investigators are always Academics supported by too rare public funding (1). As a result, except for bivalirudin, few drugs or strategies have been developed to replace older ones, or reduce the duration and number of treatments. Along with adverse events and socio-economic level, this increased number of life-long treatments on prescription is one of the reasons for poor compliance and drug discontinuation that occur in 20% to 40% of patients. More alarming, high risk patients seem to have the lowest observance, especially among active smokers and diabetic patients, with important ischemic and economic consequences (2). Studies evaluating interruption of aspirin demonstrated that what is true for the heart is also valid for the brain: it leads to a significant increase of recurrent myocardial infarction, ischemic stroke and cardiovascular death. However, the risk of spontaneous aspirin discontinuation after a long term use was not well documented before the study of Sundström et al. published in recent issue of Circulation (3).